2018
DOI: 10.1002/ncp.10236
|View full text |Cite
|
Sign up to set email alerts
|

Acute Kidney Injury Masked by Malnutrition: A Case Report and the Problem of Protein

Abstract: Acute kidney injury (AKI) is common among critically ill patients. There are a number of nutrition considerations in the management of AKI, including fluid balance, electrolyte and acid‐base disturbances, protein provision, and management of comorbid conditions. The optimal amount of protein provision for patients with AKI who are not on renal replacement therapy (RRT) has been a topic of debate for years. Excessive protein provision may contribute to azotemia in these patients, but inadequate protein intake m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 49 publications
(172 reference statements)
0
4
0
Order By: Relevance
“…While previous studies have shown that malnutrition is associated with an increased risk of developing AKI, the analysis of this population did not reveal an associated increased risk of AKI [40]. This could be due to the under-recognition of AKI in malnourished patients [41]. Serum creatinine is reflective of somatic protein stores, and these levels may be decreased in patients with malnourishment due to decreased muscle mass.…”
Section: Discussionmentioning
confidence: 58%
“…While previous studies have shown that malnutrition is associated with an increased risk of developing AKI, the analysis of this population did not reveal an associated increased risk of AKI [40]. This could be due to the under-recognition of AKI in malnourished patients [41]. Serum creatinine is reflective of somatic protein stores, and these levels may be decreased in patients with malnourishment due to decreased muscle mass.…”
Section: Discussionmentioning
confidence: 58%
“…Clinically significant acute or chronic kidney failure with GFR < 20 ml/min. Schwartz et al [ 34 ] concluded that although significant restrictions in protein intake may not be necessary for critically ill patients with acute kidney injury, excessive protein provision in these patients could have a negative effect on renal function and lead to azotaemia. For safety reasons, the GFR value is intentionally set low to exclude patients with severely restricted kidney function.…”
Section: Methods: Participants Interventions and Outcomesmentioning
confidence: 99%
“…Schwartz et al (32) concluded that although significant restrictions in protein intake may not be necessary for critically ill patients with acute kidney injury, excessive protein provision in these patients could have a negative effect on renal function and lead to azotaemia. For safety reasons, the GFR value is intentionally set low to exclude patients with severely restricted kidney function.…”
Section: Clinically Significant Acute or Chronic Kidney Failure With mentioning
confidence: 99%